Intraperitoneal Abscess in a Patient with End-stage Kidney Disease on Chronic Hemodialysis - Y J Anupama; Govindaswamy Gosikere Narasimhamurthy; Vishwanath Basavaraj; Sachin Dhanyakumar (Indian Journal of Kidney Diseases)
Intraperitoneal abscesses are a rare source of fever in patients with end-stage kidney disease (ESKD). Literature scan showed that this is mostly reported in patients undergoing peritoneal dialysis in association with episodes of peritonitis. It is not commonly reported in patients undergoing hemodialysis and hence may be overlooked. We report a case of a large, thick-walled intraperitoneal abscess in a patient with ESKD on chronic hemodialysis and review the available literature.